Penerapan Terapi Murottal Surah Ar-Rahman terhadap Penurunan Ansietas pada Pasien Stroke Hemoragik di Ruang Stroke Unit : Studi Kasus - Nurul Arsy Azizah; Citra Setyo Dwi Andhini; Endah Sari Purbaningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Hemorrhagic stroke is a condition of bleeding in the brain that can cause neurological disorders as well as psychological problems, one of which is anxiety. Unresolved anxiety can affect physiological conditions and hinder the patient's recovery process. Murottal therapy is a spiritual-based non-pharmacological intervention that can be used to help reduce anxiety levels. This study aimed to describe the implementation of murottal therapy in reducing anxiety among patients with hemorrhagic stroke in a stroke unit.This study employed a descriptive method with a case study approach involving a hemorrhagic stroke patient experiencing anxiety. Data were collected through nursing assessment, observation, the Zung Self-Rating Anxiety Scale (ZSAS), and the implementation of Surah Ar-Rahman murottal therapy. The therapy was administered for 10–15 minutes daily for three consecutive days.The results showed a 24.1% reduction in anxiety levels following the administration of murottal therapy. This was indicated by a decrease in the ZSAS score from 58 to 44 after three days of intervention. The patient appeared calmer, more relaxed, more comfortable, and was able to rest better. Murottal therapy can be used as a complementary nursing intervention to help reduce anxiety and support the recovery process in patients with hemorrhagic stroke. These findings suggest that Surah Ar-Rahman murottal therapy has the potential to become a simple, safe, cost-effective, and easily applicable spiritual nursing intervention as a complementary therapy for patients with hemorrhagic stroke.